2009
DOI: 10.3844/ajptsp.2009.107.117
|View full text |Cite
|
Sign up to set email alerts
|

Camel's Milk Protects Against Cadmium Chloride Induced Toxicity in White Albino Rats

Abstract: Problem statement:Cadmium is one of the most dangerous occupational and environmental toxins. It is found in drinking water, atmospheric air and even in food. Cadmium is reported to be very toxic to biological systems. Until now in treating intoxication with this metal, chelating Compounds have been used, burdened with numerous undesirable symptoms. For this reason, many researches are carried out in many countries to find natural-made compounds that help in the protection against cadmium induced toxicity with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
9
27
0
1
Order By: Relevance
“…In this study, Cd treated rats showed not only a significant increase in the MDA and LHP levels, but also a decrease in the activity of Catalase and glutathione and an increase in the production of oxygen reactive forms. These results support other reports where Cd was able to up-regulate oxidative stress marker such as MDA and decrease the activity of antioxidants such as GSH and Catalase [11,50]. The reduction in the lipid peroxidation as indicated by the normalization of MDA, LHP and liver antioxidants (GSH and CAT) in response to the co-administration of Se and Cd agreed well with other reports [51].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, Cd treated rats showed not only a significant increase in the MDA and LHP levels, but also a decrease in the activity of Catalase and glutathione and an increase in the production of oxygen reactive forms. These results support other reports where Cd was able to up-regulate oxidative stress marker such as MDA and decrease the activity of antioxidants such as GSH and Catalase [11,50]. The reduction in the lipid peroxidation as indicated by the normalization of MDA, LHP and liver antioxidants (GSH and CAT) in response to the co-administration of Se and Cd agreed well with other reports [51].…”
Section: Discussionsupporting
confidence: 93%
“…These complexes are inert and excreted via bile, so decreased GSH might have been due to its consumption during the Cd detoxification [54]. The catalase activities were decreased in the liver extracts of the Cd than the control rats which agreed with the earlier studies [50]. Inhibition of catalase after Cd treatment may be due to the depletion of Se in Cd detoxification.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Antimicrobial activities of camel’s milk proteins were also investigated (El-Agamy et al 1992). In addition, camel’s milk has antitoxic effect against cadmium chloride (Al-Hashem et al 2009; Dallak 2009), CCl 4 (Khan and Alzohairy 2011), Cisplatin (Afifi 2010), Paracetamol (Al-Fartosi et al 2011), Aluminum chloride (Al-Hashem 2009). Although, Khan and Alzohairy (2011) studied the protective effect of camel’s milk against CCl 4 induced hepatotoxicity, biochemical parameters such as Kidney biomarkers and lipoprotein profiles were not fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in the serum albumin concentration was observed in the rats that received camel milk either alone or with bee honey compared with the CCl 4 -treated group. The increased albumin concentration after the camel milk and bee honey treatment could be attributed either to their nutritional values or to decreased lipid peroxidation and increased plasma protein thiol activities(Al-Fartosi et al 2012;Al-Hashem et al 2009b).…”
mentioning
confidence: 98%